Pengaruh Suhu dan Lama Pengeringan Terhadap Sifat Kimia dan Fisik Serbuk Bit Merah (Beta vulgaris L.) - Harmaili Sangga; Nugraheni Widyawati (Jurnal Teknologi dan Industri Pertanian Indonesia, 2021)
Beetroot plant or Beta vulgaris L. is one of the horticultural plants which is widely cultivated in various regions of Indonesia. It is because the advantage of the beet plant and its use as a natural red dye powder for food ingredients. Beetroot powder can be produced through the drying or withering method using a draying oven and the use of a drying agent to maintain the quality product during drying. This study aims to determine the effect of temperature treatment and drying time on betasianin,% water level,% yield, vitamin C and organoleptic tests (color and aroma) for the natural dye of beetroot powder. This research used a randomized block design  with two (2) factors treatment with 4 replications in order to obtain 24 trials. The treatment factors used were (S) temperature (60°C and 70°C) and (T) drying time (10, 11, and 12 hours). The results of the research of the treatment interaction between temperature and drying time obtained the yield content of the average value was 13% with the water level for the material with the highest average value of 7% at 600C for 10 hours and the lowest was 5% at 700C for 12 hours. For the vitamin C content of beet powder obtained the highest average value on 1.35 mg at  600C for 10 hours. At 600C for 10, the highest betasianin content was 0.151 mg / L. From the organoleptic results, the preferred color of beet powder was at 600C (11 hours) and the preferred aroma was 700C (10 hours).